Gender-Related Characterization of Acne in Chinese: A Multiple-Center Cross-Sectional Survey on 13085 Cases - Zhu T; Ge Y; Zhang J; Chen Y; Zhong H; Yang L; Zhang J; Li K; Yang S (Clinical, Cosmetic and Investigational Dermatology)
Tingting Zhu,1,* Yiping Ge,2,* Jiechen Zhang,3,* Yan Chen,4 Huajie Zhong,5 Li Yang,6 Juan Zhang,7 Ke Li,8 Shuyun Yang9 1Department of Dermatology, The First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of China; 2Department of Cosmetic Laser Surgery, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, People’s Republic of China; 3Department of Dermatology, Tongren Hospital Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 4Department of Dermatology, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 5Department of Dermatology, Affiliated Huzhou Hospital, Zhejiang University School of Medicine, Huzhou, Zhejiang, People’s Republic of China; 6Department of Dermatology, Henan Provincial People’s Hospital, The People’s Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of China; 7Department of Dermatology, The First Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, People’s Republic of China; 8Department of Burn and Plastic Surgery, The First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of China; 9Department of Dermatology, The People’s Hospital of Baoshan/Fifth Affiliated Hospital of Dali University, Baoshan, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuyun Yang, Department of Dermatology, The People’s Hospital of Baoshan/Fifth Affiliated Hospital of Dali University, Baoshan, Yunnan, 678000, People’s Republic of China, Email yy090821@yeah.net Ke Li, Email likefggf@163.comBackground: Acne is a common inflammatory dermatosis. Although gender-related differences in prevalence and age of onset have been documented. Other gender-related characteristics of acne have not been well elucidated yet.Objective: We compared characteristics of skin lesions, severity and risk factors of acne between males and females in Chinese.Methods: Investigator-administered questionnaire was used to collect demographic data, clinical feature and risk factors of acne from May 2020 to August 2021. All participants were from outpatient clinics in seven cities, China.Results: A total of 13085 participants, including 4746 males (36.27%) and 8339 females (63.73%), aged 8 to 35 years old, completed the questionnaire. The age of onset of acne was significantly younger in males than in females(p< 0.001). More females than males had comedones(83.76% vs 75.22%, p< 0.001). In contrast, more males than females had pustules, cyst/nodules, scars and severer lesions(p< 0.001). Moreover, the major risk factors for acne were constipation, cosmetics, dairy and sweet foods for females, while the major risk factors for males were computer usage/playing electronic games, staying up late at night, intake of hot or spicy foods. More females than males experienced good response to photodynamic treatment(79.52% vs 52.86%, p< 0.05).Conclusion: Acne appears earlier in males than in females. Clinical features and risk factors for acne differ between males and females. More females than males experience good response to photodynamic therapy.Limitation: This questionnaire survey was carried out in Chinese aged 8 to 35 years old. Gender-related characteristics in other ages and regions remain to be explored.Keywords: acne, risk factors, gender, severity, treatment